Comparatyve analysis of using terms in mathematic textbook separate school - Kaklauskienė, Dalia (Lietuvos matematikos rinkinys, 2005)
The article deals with the scope of lexical units textbooks on mathematics for ten-year schools, frequencies of title words are compared. Mathematical terms occurring in the texts are selected, their frequencies regarding separate school grades have been investigated.